Geological reservoir modelling for Whicher Range Field tight gas sand - Orsini Martin, Cesar Daniel (Curtin University, 2013)
A poor understanding of the reservoir properties within the Whicher Range area has led to unsuccessful exploration and appraisal strategies. A key driver for this research is to develop a geological reservoir model on the tight gas sand Permian section in the southern Perth Basin that contribute to the development and production of the field by integrating core, well logs and analogue data within a sequence stratigraphic framework and generating a plausible depositional model that constrained the reservoir architecture and facies distribution over the field.